Understanding Characterisation of Managerial Process : Is It Useful For Managers ? - Chariri, Anies (JURNAL BISNIS STRATEGI, 1997)
Some  research findings  indicate  that there  are different  views of what managers  really  do  in  managing their  organisations.   One of them shows  that  what  managers  actually do  cannot  be classified into  planning, organising,  leading,  and controlling. As a result,  one might claim that understanding  characterisation of managerial process  is useless. However,   in this paper  it  is argued  that understanding  characteristics  of mana gerial process    is useful for  managers  to help them   cope with the  rapid changes   in  business  environment. It  is also claimed that  managerial process is  a political  system  and a game that  take place  in a wide  arena.  It  is highly  interdependent,  contextual,   less systematic,  and    changeable. Managerial process   also  involves the need for  setting  agenda, building network,  and managing discourses,   interactions,  symbols, and organisational politics. Finally,  it is believed  that understanding  characterisation  of managerial process   lead managers  to have  deep  understanding  of organisational dynamics and changes  in business  environment,   and  to have special  skills  that are required to cope with  the  changing  environment.